Global perspectives and transdisciplinary opportunities for locust and grasshopper pest management and research - Word Ries, Mira; Adriaansen, Chris; Aldobai, Shoki; Berry, Kevin; Bal, Amadou Bocar; Catenaccio, María Cecilia; Cigliano, María Marta; Cullen, Darron A.; Deveson, Ted; Diongue, Aliou; Foquet, Bert; Hadrich, Joleen; et al. (Pensoft Publishers, 2024)
Locusts and other migratory grasshoppers are transboundary pests. Monitoring and control, therefore, involve a complex system made up of social, ecological, and technological factors. Researchers and those involved in active management are calling for more integration between these siloed but often interrelated sectors. In this paper, we bring together 38 coauthors from six continents and 34 unique organizations, represent ing much of the social-ecological-technological system (SETS) related to grasshopper and locust management and research around the globe, to introduce current topics of interest and review recent advancements. To gether, the paper explores the relationships, strengths, and weaknesses of the organizations responsible for the management of major locust-affect ed regions. The authors cover topics spanning humanities, social science, and the history of locust biological research and offer insights and ap proaches for the future of collaborative sustainable locust management These perspectives will help support sustainable locust management, which still faces immense challenges such as fluctuations in funding, fo cus, isolated agendas, trust, communication, transparency, pesticide use, and environmental and human health standards. Arizona State University launched the Global Locust Initiative (GLI) in 2018 as a response to some of these challenges. The GLI welcomes individuals with interests in lo custs and grasshoppers, transboundary pests, integrated pest management, landscape-level processes, food security, and/or cross-sectoral initiatives.